Preliminary report on the safety and utility of a novel automated mechanical endoscopic tissue resection tool for endoscopic necrosectomy: a case series - van der Wiel, S. E.; May, A.; Poley, J. W.; Grubben, M. J. A. L.; Wetzka, J.; Bruno, M. J.; Koch, A. D. (Endoscopy International Open, 2020)
Background and study aims Endoscopic drainage of walled-off necrosis and subsequent endoscopic necrosectomy has been shown to be an effective step-up management strategy in patients with acute necrotizing pancreatitis. One of the limitations of this endoscopic approach however, is the lack of dedicated and effective instruments to remove necrotic tissue. We aimed to evaluate the technical feasibility, safety, and clinical outcome of the EndoRotor, a novel automated mechanical endoscopic tissue resection tool, in patients with necrotizing pancreatitis.Methods Patients with infected necrotizing pancreatitis in need of endoscopic necrosectomy after initial cystogastroscopy, were treated using the EndoRotor. Procedures were performed under conscious or propofol sedation by six experienced endoscopists. Technical feasibility, safety, and clinical outcomes were evaluated and scored. Operator experience was assessed by a short questionnaire.Results Twelve patients with a median age of 60.6 years, underwent a total of 27 procedures for removal of infected pancreatic necrosis using the EndoRotor. Of these, nine patients were treated de novo. Three patients had already undergone unsuccessful endoscopic necrosectomy procedures using conventional tools. The mean size of the walled-off cavities was 117.5 ± 51.9 mm. An average of two procedures (range 1 – 7) per patient was required to achieve complete removal of necrotic tissue with the EndoRotor. No procedure-related adverse events occurred. Endoscopists deemed the device to be easy to use and effective for safe and controlled removal of the necrosis.Conclusions Initial experience with the EndoRotor suggests that this device can safely, rapidly, and effectively remove necrotic tissue in patients with (infected) walled-off pancreatic necrosis.